2010
DOI: 10.1088/0004-637x/722/1/880
|View full text |Cite
|
Sign up to set email alerts
|

GROUND-BASED MULTISITE OBSERVATIONS OF TWO TRANSITS OF HD 80606b

Abstract: We present ground-based optical observations of the September 2009 and January 2010 transits of HD 80606b. Based on 3 partial light curves of the September 2009 event, we derive a midtransit time of T c [HJD] = 2455099.196 ± 0.026, which is about 1σ away from the previously predicted time. We observed the January 2010 event from 9 different locations, with most phases of the transit being observed by at least 3 different teams. We determine a midtransit time of T c [HJD] = 2455210.6502 ± 0.0064, which is withi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
27
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 41 publications
5
27
1
Order By: Relevance
“…In addition, Hébrard et al (2010) found their R p /R * value differed by 3σ compared to the results obtained by both Pont et al (2009) and Winn et al (2009). Shporer et al (2010) launched a multiple-site ground-based observation of the same transit in an attempt to confirm the Hébrard et al (2010) timing discrepancy. Their midtransit time was 12 minutes earlier than predicted and within 1.3σ of Hébrard et al (2010).…”
Section: Winn Et Al (2009) Also Confirmed a Spin-orbit Misalignment mentioning
confidence: 88%
See 3 more Smart Citations
“…In addition, Hébrard et al (2010) found their R p /R * value differed by 3σ compared to the results obtained by both Pont et al (2009) and Winn et al (2009). Shporer et al (2010) launched a multiple-site ground-based observation of the same transit in an attempt to confirm the Hébrard et al (2010) timing discrepancy. Their midtransit time was 12 minutes earlier than predicted and within 1.3σ of Hébrard et al (2010).…”
Section: Winn Et Al (2009) Also Confirmed a Spin-orbit Misalignment mentioning
confidence: 88%
“…Hébrard et al (2010) discovered their mid-transit time to be approximately 24 minutes earlier than the value predicted by Winn et al (2009). In addition, Hébrard et al (2010) found their R p /R * value differed by 3σ compared to the results obtained by both Pont et al (2009) and Winn et al (2009). Shporer et al (2010) launched a multiple-site ground-based observation of the same transit in an attempt to confirm the Hébrard et al (2010) timing discrepancy.…”
Section: Winn Et Al (2009) Also Confirmed a Spin-orbit Misalignment mentioning
confidence: 89%
See 2 more Smart Citations
“…LCOGT also participates in follow-up studies of known transiting exoplanets. For example, Hidas et al (2010) and Shporer et al (2010a) describe two follow-up campaigns led by LCOGT researchers where a complete coverage of HD 80606b 12 hour transits was obtained.…”
mentioning
confidence: 99%